Epidermal growth factor receptor mutation‐positive advanced lung adenocarcinoma presenting with acute respiratory failure diagnosed by thin bronchoscope through transnasal route under high‐concentration oxygen mask. Issue 9 (9th August 2022) - Ito, Takayasu; Makino, Yasushi; Mashimo, Shuko; Baba, Tomoya; Otsuki, Ryo; Yasui, Hirotoshi; Fukui, Yasutaka; Odate, Mitsuru; Arai, Yoshifumi; Okachi, Shotaro; Wakahara, Keiko; Hashimoto, Naozumi
Abstract: A 59‐year‐old woman complained of continuous dyspnea. Computed tomography revealed multiple pulmonary nodules, mildly small enlarged mediastinal lymph nodes and a nodule in the liver segment 8. Her dyspnea worsened with respiratory failure 4 days after presentation. Liver biopsy was not possible as she could not hold her breath; thus, we performed bronchoscopy. For biopsy, the pulmonary nodules with a positive bronchus sign were preferred over the mildly small enlarged mediastinal lymph nodes. Bronchoscopy under non‐invasive positive pressure ventilation (NPPV) or high‐flow nasal cannula (HFNC) was impossible because of the lack of equipment. Therefore, we biopsied via thin bronchoscope through nasal cavity under a high‐concentration oxygen mask. Pathological findings revealed epidermal growth factor receptor mutation‐positive lung adenocarcinoma. For patients with respiratory failure who cannot undergo bronchoscopy under NPPV or HFNC, thin bronchoscopy through the nasal cavity under a high‐concentration oxygen mask may be clinically useful to prevent hypoxaemia during the procedure Abstract : We report the case of a patient with acute respiratory failure who was diagnosed with epidermal growth factor receptor (EGFR) mutation‐positive advanced lung adenocarcinoma via thin bronchoscope through the nasal cavity under a high‐concentration oxygen mask, which was performed to prevent hypoxaemia during bronchoscopy.